Aplicação foliar de biofertilizante em alface semi-hidropônica fertigada com solução salina - Guimarães, Ítala Tavares (Universidade Federal Rural do Semi-Árido, 2017)
Water scarcity in the world is a problem diagnosed, especially in countries with large semi-arid regions such as Brazil. Researches have been developed with a view to making the use of saline waters as an input for cultivation, mainly hydroponics, with a focus mainly on lettuce, the most prominent leafy vegetable in Brazil. The objective of this work was to evaluate the development of lettuce in a semi-hydroponic system fertigated with saline water and fertilization with biofertilizer via foliar. The present work was carried out in a greenhouse located in the experimental area of the Department of Environmental and Technological Sciences (DCAT) of the Federal Rural Semiarid University (UFERSA), in the municipality of Mossoró, RN (5 ° 11'31 "S, 37 ° 20'40 "W, mean altitude of 18 m) from August to September 2017. The experimental design was a randomized complete block design, with treatments arranged in a 2 x 4 factorial scheme, with 4 replications, two salinity levels of the water used in the preparation of the nutrient solution (0.5 and 3.5 dS m-1) and four biofertilizer concentrations (0, 20, 40 and 60%) applied by foliar spraying. The evaluated characteristics were: crown diameter, stem diameter, number of leaves, fresh mass, dry mass, leaf succulence, leaf area and specific leaf area. The use of saline water in the preparation of the nutrient solution reduces the production of fresh mass and dry mass in the lettuce crop. The biofertilizer can be applied via foliar with concentration of up to 20%, promoting greater plant growth.
Monografia
Keywords: Lactuca sativa; Hidroponia; Salinidade; Lactuca sativa; Hydroponics; Salinity; CIENCIAS AGRARIAS::AGRONOMIA